Observation of the χc2(2P) meson in the reaction γγ→ DD̄ at BABAR - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2010)
A search for the Z(3930) resonance in γγ production of the DD̄ system has been performed using a data sample corresponding to an integrated luminosity of 384fb-1 recorded by the BABAR experiment at the PEP-II asymmetric-energy electron-positron collider. The DD̄ invariant mass distribution shows clear evidence of the Z(3930) state with a significance of 5.8σ. We determine mass and width values of (3926.7±2. 7±1.1)MeV/c2 and (21.3±6.8±3.6)MeV, respectively. A decay angular analysis provides evidence that the Z(3930) is a tensor state with positive parity and C parity (JPC=2++); therefore we identify the Z(3930) state as the χc2(2P) meson. The value of the partial width Γγγ×B(Z(3930)→DD̄) is found to be (0.24±0.05±0.04)keV. © 2010 The American Physical Society.